Grape seed proanthocyanidin extract inhibits DNA and protein damage and labile iron, enzyme, and cancer cell activities - Hosam M. Habib; Esmail M. El-Fakharany; E. Kheadr; Wissam H. Ibrahim (Scientific Reports, 2022)
Abstract Grape seed extract from (Vitis vinifera) (VGSE) is an excellent source of various polyphenols that exhibit highly potent antioxidant and disease prevention properties. Although numerous biological activities, with potential for improving human health, have been reported for VGSE, there is a lack of data relating to the health benefits of VGSE on DNA damage, protein damage, labile iron activity, and enzyme inhibitory effects. This investigation demonstrated, for the first time, that VGSE inhibits DNA and BSA damage and labile iron activity in-vitro. Moreover, VGSE also inhibited in-vitro activities of AChE, tyrosinase, and α-amylase. VGSE treatment significantly reduced viability of MCF-7, Hep-G2, Caco-2, and Huh-7 cells after 48-h treatments. The results obtained provide additional support for the purported health benefits of VGSE and reinforce its potential in disease prevention and therapy, especially in relation to cancer.